(untitled) (Международный научный журнал «Инженер», 2026)
This article examines the defects occurring in rails used on the high-speed sections of Uzbekistan Railways. Additionally, the impact of train movements on the rails is considered. The article mainly focuses on rails and the frequently occurring defects in them. Since rails hold a special place, great attention is paid to the development of technologies that assess all problems related to rails and the metallurgical industry, as well as the defects and damages that serve as the basis for evaluating rail conditions. The article also considers the high-speed section of the Tashkent - Samarkand railway line as the main object of study.